FACTORS INFLUENCING TELEHEALTH UTILIZATION IN MENTAL HEALTH SERVICES: SYSTEMATIC LITERATURE REVIEW - Khansa Fatihah Muhammad; Anhari Achadi (Journal of Community Mental Health and Public Policy)
Background: Mental health is an increasing concern in public policy, demanding better services and support. Consultations and treatments for mental health can be accessed through online services via telehealth. While telehealth offers advantages for mental health services, it also presents challenges, necessitating improvements in quality to enhance service delivery. Purpose: This journal aims to explore factors influencing the use of telehealth for mental health services, focusing on technology, telehealth quality, and other relevant aspects. Methods: A systematic literature review was conducted using articles sourced from Google Scholar, Garuda, and ProQuest. Results: Telemedicine, as a component of telehealth, has emerged as a vital alternative to in-person mental health care. Despite challenges such as limited technological access and privacy concerns, electronic and telephone-based platforms have demonstrated the potential to empower patients and enhance care accessibility. Conclusion: The increasing importance of mental health has raised demand for efficient digital solutions like telehealth, which can lower costs and improve service access. However, expanding telehealth requires addressing challenges such as technological limitations, privacy issues, and the need for supportive policies. Tackling these issues is essential for integrating telehealth into mainstream mental health services and ensuring sustainable growth.